2020
DOI: 10.1177/0960327120959417
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin attenuates chemical-induced cardiotoxicity

Abstract: Environmental chemicals and drugs can induce cardiotoxicity, mainly by generating free radicals. Reactive oxygen species play a critical role in the pathogenesis of cardiac tissue injury. This highlights a need for prevention of cardiotoxicity by scavenging free radicals. Melatonin has been shown to act as a protector against various conditions in which free radicals cause molecular and tissue injury. Some of the mechanisms by which melatonin operates as a free radical scavenger and antioxidant have been ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
(150 reference statements)
0
7
0
1
Order By: Relevance
“…Different drugs such as Luzindole work as receptor blockers, with an important role in cardiac tissue. Luzindole and 4P-PDOT competitively block MT1 melatonin receptors (in concentrations higher than 300 nM), and both are inverse agonists in systems with constitutively active MT1 receptors [148][149][150][151][152][153][154][155]159].…”
Section: Melatonin Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different drugs such as Luzindole work as receptor blockers, with an important role in cardiac tissue. Luzindole and 4P-PDOT competitively block MT1 melatonin receptors (in concentrations higher than 300 nM), and both are inverse agonists in systems with constitutively active MT1 receptors [148][149][150][151][152][153][154][155]159].…”
Section: Melatonin Receptorsmentioning
confidence: 99%
“…The molecular mechanisms underlying those processes are still not fully elucidated. The role of melatonin as a cardioprotective molecule has been suggested as part of a pathway linked with its antioxidative action in the heart [ 149 ]. However, other mechanisms related to ion channel interaction as well as positive effects in mitochondria define its cardioprotective action too.…”
Section: Melatonin As a Potential Antiarrhythmic Treatment In Aginmentioning
confidence: 99%
“…(2023) showed that quantum descriptors can provide valuable insights into the electronic structure of biological macromolecules relevant to processes such as catalysis and protein binding 58 . However, the intermediate values of Comp4, particularly its second highest chemical potential ( μ ), may indicate possible interactions with DNA or generation of cardiotoxic reactive oxygen species 59 . In contrast, Comp1, with its increased reactivity and electrophilicity, raises concerns about off‐target effects and potential damage to DNA and cell membranes 60,61 .…”
Section: Discussionmentioning
confidence: 99%
“… 58 However, the intermediate values of Comp4, particularly its second highest chemical potential ( μ ), may indicate possible interactions with DNA or generation of cardiotoxic reactive oxygen species. 59 In contrast, Comp1, with its increased reactivity and electrophilicity, raises concerns about off‐target effects and potential damage to DNA and cell membranes. 60 , 61 Comp2 might have limited cellular penetration and lower binding affinity to target biomolecules due to its pronounced electronegativity.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin acts to detoxify free radicals such as hydroxyl by donating electrons directly. This substance protects cells, tissues, and organs from oxidative damage induced by various free radical production processes and agents (21). It is effective in safeguarding nuclear DNA, membrane fats, and cytoplasmic proteins and improves the antioxidant defense capacity of the whole organism.…”
Section: Introductionmentioning
confidence: 99%